قاعدة: "لا ضر ولا ضرار" وتطبيقاتها في العلاقة بين الحاكم والمحكوم بدولة الامارات العربية المتحدة - Al-Hana'i, Adil; Amanullah, Muhammad (Design for Scientific Renaissance SDN BHD, 2018)
This paper aims to discuss the principle of La ḍarar wala ḍirār as one of the major jurisprudent principles, and to discuss the explanation of contemporary application as well of the principle on the relationship between the United Arab Emirates government and its citizens. Inasmuch as Shar’ah politics is dependent on bringing interests on the one hand and preventing evil on the other hand, hence this research came to explain what is meant by the harm (Ḍarar), that is to be prevented in Islamic jurisprudence. The researcher uses the analytical method to address the jurists’ views about the principle and its application, as well as to consider the issues related to the principle in the Shari'a courts of the United Arab Emirates. The research has revealed that the Shar’ah courts depend on the principle of La ḍarar wala ḍirār in resolving the dispute between the adversaries. The research has also recommended the need to address the issues of Islamic courts related to the principle from different angles.